Method for purifying nanoparticles, nanoparticle composition, and method for producing nanoparticle composition
By using associative ligands in low-polarity solvents to contact nanoparticles, the content of perovskite-type crystal structure can be selectively increased, solving the problems of high-temperature synthesis and crystallization phase change, and realizing the purification of perovskite-type quantum dots with stable α phase at low temperature and the preparation of compositions.
Patent Information
- Application Number
- CN202480033439.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-19
- Filing Date
- 2024-05-10
- Publication Date
- 2026-01-13
AI Technical Summary
Existing technologies require high temperatures to synthesize perovskite quantum dots, and the crystalline phase is prone to change over time, making it difficult to selectively generate and maintain the α phase at low temperatures.
A method was adopted to contact nanoparticles with associative ligands in a low-polarity solvent. By selectively increasing the content of perovskite-type crystal structure, a nanoparticle dispersion was prepared, ensuring that the nanoparticle composition retains the α phase at a lower temperature.
Obtaining and maintaining the α-phase perovskite quantum dots at lower temperatures improves their stability and spectral sensitivity.
Smart Images

Figure CN121335864A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to a method for purifying nanoparticles, a nanoparticle composition, and a method for manufacturing a nanoparticle composition. BACKGROUND
[0002] Quantum dots having a perovskite-type crystal structure are known to have a narrow half-width in spectral sensitivity characteristics, and exhibit high color purity, and thus are applied to organic EL materials, quantum dot light emitting materials, and solar cell materials. In addition, since the absorption and emission wavelengths can be controlled by the composition of halogen, there is an advantage that a material that can easily provide a light response to a wide wavelength range can be provided.
[0003] Quantum dots having a peroviskite-type crystal structure are known to have various crystalline phases depending on the synthesis conditions and storage conditions (Phys. Rev. Materials, 3, 113605). The light emitting characteristics and power generation characteristics are highly affected by the type of crystalline phase. The phase that exhibits the best characteristics is the α phase, but the α phase is a high-temperature stable phase, and thus it is difficult to selectively produce the α phase by a general synthesis method.
[0004] In Angew. Chem. Int., Ed. 2018, 57, 9083-9087, quantum dots having an α phase were obtained by synthesizing quantum dots at a high temperature condition of 260°C while reacting with oleylamine hydriodide.
[0005] Prior art documents
[0006] Non-patent literature
[0007] Non-Patent Literature 1: Phys. Rev. Materials, 3, 113605
[0008] Non-Patent Literature 2: Angew. Chem. Int., Ed. 2018, 57, 9083-9087 SUMMARY
[0009] PROBLEMS TO BE SOLVED BY THE INVENTION
[0010] However, the synthesis method described in Angew. Chem. Int., Ed. 2018, 57, 9083-9087 requires a high temperature condition of 260°C, and thus limits industrial applications. In addition, the quantum dots obtained by the synthesis method described in Angew. Chem. Int., Ed. 2018, 57, 9083-9087 have a problem that the crystalline phase gradually changes from the α phase to another phase over time.
[0011] The present application was made in view of the above problems, and aims to provide a method for purifying nanoparticles that can obtain an α phase under lower temperature conditions. Furthermore, the present application aims to provide a nanoparticle composition that can maintain an α phase even over time.
[0012] Solution to the problem
[0013] The method for purifying nanoparticles according to the embodiment of the present application includes a step of preparing nanoparticles having a perovskite crystal structure as a polymorph and including a plurality of crystal structures, a step of preparing a ligand solution containing a solvent having a relative dielectric constant of a prescribed value or less and an associative ligand containing a main chain having a plurality of carbon atoms and a polar group having a polarity higher than the main chain and self-associating in the solvent, and a step of preparing a nanoparticle dispersion liquid by bringing the nanoparticles and the ligand solution into contact with each other, wherein the step of preparing the nanoparticle dispersion liquid includes a step of selectively increasing a proportion of a content of a prescribed crystal structure among the plurality of crystal structures.
[0014] The method for manufacturing a nanoparticle composition according to the embodiment of the present application includes a step of preparing nanoparticles having a perovskite crystal structure as a polymorph and including a plurality of crystal structures, a step of preparing a ligand solution containing a solvent having a relative dielectric constant of a prescribed value or less and an associative ligand containing a main chain having a plurality of carbon atoms and a polar group having a polarity higher than the main chain and self-associating in the solvent, and a step of preparing a nanoparticle dispersion liquid by bringing the nanoparticles and the ligand solution into contact with each other, wherein the step of preparing the nanoparticle dispersion liquid includes a step of selectively increasing a proportion of a content of a prescribed crystal structure among the plurality of crystal structures.
[0015] The nanoparticle composition according to the embodiment of the present application contains nanoparticles having a perovskite crystal structure as a polymorph and an associative ligand containing a main chain having a plurality of carbon atoms and a polar group having a polarity higher than the main chain, wherein at least a part of the associative ligand is coordinated to the nanoparticles via the polar group to change a crystal structure of the nanoparticles.
[0016] The nanoparticle composition according to the embodiment of the present application contains a solvent having a relative dielectric constant of a prescribed value or less, nanoparticles having a perovskite crystal structure as a polymorph, and a plurality of ligands each containing a main chain having a plurality of carbon atoms and a polar group having a polarity higher than the main chain, wherein the plurality of ligands contain a first component constituting a reverse micelle-like structure in the solvent and a second component coordinated to a surface of the nanoparticles.
[0017] Advantages of the invention
[0018] According to the present application, it is possible to provide a purification method of nanoparticles, which can obtain an alpha phase under a lower temperature condition. Further, according to the present application, it is possible to provide a nanoparticle composition, which can maintain an alpha phase even over time. BRIEF DESCRIPTION OF DRAWINGS
[0019] [ Fig. 1A ] is a flowchart of a manufacturing method of a nanoparticle composition according to the first embodiment.
[0020] [ Fig. 1B ] is a flowchart of a purification method of nanoparticles according to the first embodiment.
[0021] [ Fig. 2A ] is a diagram schematically showing structures of a nanoparticle P and a ligand solution Q (60-1 to 60-4) according to the first embodiment.
[0022] [ Fig. 2B ] is a diagram schematically showing structures of a nanoparticle P and a ligand solution Q (60-1 to 60-4) according to the first embodiment.
[0023] [ Fig. 2C ] is a diagram schematically showing structures of a nanoparticle P and a ligand solution Q (60-1 to 60-4) according to the first embodiment.
[0024] [ Fig. 2D ] is a diagram schematically showing structures of a nanoparticle P and a ligand solution Q (60-1 to 60-4) according to the first embodiment.
[0025] [ Fig. 3A ] is a diagram schematically showing structures of a nanoparticle composition according to the second embodiment.
[0026] [ Fig. 3B ] is a diagram schematically showing structures of a nanoparticle composition according to the second embodiment.
[0027] [ Fig. 4A ] is a diagram schematically showing structures of a nanoparticle composition according to the third embodiment.
[0028] [ Fig. 4B ] is a diagram schematically showing structures of a nanoparticle composition according to the third embodiment.
[0029] [ Fig. 5 ] is a diagram schematically showing a wavelength conversion layer and a display device including a nanoparticle composition according to the fourth embodiment. DETAILED DESCRIPTION
[0030] The preferred embodiments of the present application will now be described in detail with reference to the accompanying drawings. The size, material, shape, and relative arrangement of the components described in these embodiments are not intended to limit the scope of the present application.
[0031] <First Embodiment>
[0032] Using Fig. 1A , Fig. 1B and Figs. 2A to 2D The manufacturing method and constitution of the nanoparticle composition according to the first embodiment and the purification method of the nanoparticle are described.
[0033] As Fig. 1A indicated, the manufacturing method 1000 of the nanoparticle composition according to the first embodiment includes at least the S103, S105, S107, and S109 steps between the start step S101 and the end step S111.
[0034] (S103)
[0035] The step S103 is a step of preparing the nanoparticle A having a perovskite-type crystal structure as a polymorph and containing a plurality of crystal structures.
[0036] (S105)
[0037] The step S105 is a step of preparing a ligand solution B containing a solvent 10 having a relative dielectric constant of a prescribed value or less and an associative ligand 60 having a main chain 40 containing a plurality of carbon atoms and a polar group 50 having a polarity higher than that of the main chain 40 and self-associating in the solvent 10.
[0038] (S107, S109)
[0039] The step S107 is a step of preparing a nanoparticle dispersion liquid C by bringing the nanoparticle P and the ligand solution Q into contact with each other, and includes the step S109 of selectively increasing the proportion of the content of the prescribed crystal structure among the plurality of crystal structures.
[0040] The manufacturing method 1000 of the nanoparticle composition according to the present embodiment includes the step S109 of selectively increasing the proportion of the content of the prescribed crystal structure corresponding to the nanoparticle P among the plurality of crystal structures, and thus can be paraphrased as a purification method 1000 of the nanoparticle.
[0041] In the manufacturing method 1000 of the nanoparticle composition, regarding the mechanism of selectively increasing the proportion of the content of the prescribed crystal structure, the present inventors consider as follows.
[0042] First, it is a premise that the nanoparticle P having a perovskite crystal structure as a polymorph is unstable to a polar material, and therefore, when the nanoparticle P is dispersed and supported in a solvent, it is necessary to disperse the nanoparticle P in a solvent (low-polarity solvent) having a relative dielectric constant of a prescribed value or less.
[0043] Second, in order to protect the nanoparticle P having a perovskite crystal structure as a polymorph, it is considered to coordinate a ligand having a polar group to the surface of the nanoparticle P.
[0044] Since the ligand containing a polar group has a low affinity to a low-polarity solvent, it is not possible to allow a large amount of the ligand to act on the nanoparticle P. In contrast, the associating ligand 60 exhibiting self-association in the relationship with the solvent, when the polar groups 50 associate with each other, the apparent polarity is lowered, and the polar moiety is allowed to exist at a high concentration even in a low-polarity solvent (ligand solution Q). In the present specification, the self-association of the ligand means a property of taking a form of a reverse micelle-like structure having a nonpolar group facing the solvent side by at least any one of association of a single ligand itself and association of a plurality of relevant ligands.
[0045] When the ligand solution Q and the nanoparticle P are brought into contact with each other, a component 60-a in which at least a part of the self-associated associating ligand 60 is dissociated and a component 60-b in which the self-association is maintained are generated in the solvent 10. It is inferred that the dissociated ligand 60-a of the associating ligand 60 coordinates to the surface of the nanoparticle P. It can be restated that at least a part of the nanoparticle P is protected so as to be introduced into the associated portion of the associating ligand 60. The plurality of polar groups 50 of the associating ligand 60 all coordinate to the surface of the nanoparticle P at the same time. The present inventors infer that a change toward the α phase which is a high-temperature stable phase is induced by using such a sharp coordination as a driving force.
[0046] (Self-association)
[0047] In the present embodiment, the self-association means association by electrostatic interaction of at least a part of the polar groups 50 in the solvent 10 having a relative dielectric constant of a prescribed value or less. The polar groups 50 do not necessarily have to interact with each other directly, and a trace amount of a polar material such as water can intervene therebetween. Furthermore, as shown in Fig. 2B Self-association can be intermolecular association (60-1) or intramolecular association (60-2). Furthermore, even when different types of polar groups associate with each other by electrostatic interaction and constitute a reverse micelle-like structure with respect to the common solvent 10, it is regarded as self-association.
[0048] (Nanoparticle)
[0049] The nanoparticle P in the present embodiment is a nanoparticle including a nanocrystal having a perovskite-type crystal structure in which A site (monovalent cation), B site (divalent cation), and X site (monovalent anion including halide anion) as a structural component as an allotrope. The perovskite-type crystal structure is restated as a perovskite structure, ABX3-type crystal structure, or ABX3-type structure. In addition, a double perovskite-type crystal structure represented by A2B1B2X6 is also included in the perovskite-type crystal structure. In the present specification, the nanoparticle P can be restated as a luminescent nanoparticle, luminescent nanocrystal, photoresponsive nanocrystal, or quantum dot.
[0050] As the average particle diameter of the nanoparticle, the particle diameter of the nanoparticle is preferably 1 nm or more and 30 nm or less, and more preferably 2 nm or more and 25 nm or less. If the average particle diameter is less than 1 nm, the stability can be insufficient. If the average particle diameter is more than 30 nm, the dispersibility in a medium can be insufficient.
[0051] [A site of perovskite structure]
[0052] As the A site, a monovalent cation is employed. Examples of the monovalent cation for the A site include nitrogen-containing organic compound cations such as ammonium cation (NH4 + ), alkylammonium cation having 6 or less carbon atoms, formamidinium cation (HC(NH2)2 + ), guanidinium cation (C(NH2)3 + ), imidazolium cation, pyridinium cation, and pyrrolidinium cation, and alkali metal cations such as lithium cation (Li + ), sodium cation (Na + ), potassium cation (K + ), rubidium cation (Rb + ), and cesium cation (Cs + ).
[0053] These monovalent cations employed in the A site have a small ionic diameter and have a size sufficient to be embedded in a crystal lattice, and thus a perovskite compound can form a stable three-dimensional crystal.
[0054] Preferred examples of the alkylammonium cation having 6 or less carbon atoms include methylammonium cation (CH3NH3 + ), ethylammonium cation (C2H5NH3 + ), and propylammonium cation (C3H7NH3 + ).
[0055] From the viewpoint of obtaining high luminous efficiency, it is preferable to use at least any of a methylammonium cation, a formamidinium cation, and a cesium cation as the A site, and from the viewpoint of suppressing color change, the A site is more preferably a cesium cation. These monovalent cations can be used in combination of two or more for the A site.
[0056] When the A site is a cesium cation, a cesium salt is used as a raw material for synthesizing the nanoparticles. As the cesium salt, cesium chloride, cesium bromide, cesium iodide, cesium hydroxide, cesium carbonate, cesium bicarbonate, cesium hydrogen carbonate, cesium formate, cesium acetate, cesium propionate, cesium neopentanoate, or cesium oxalate is suitably used. Depending on the synthesis method, an appropriate cesium salt among these cesium salt candidates can be used.
[0057] When the A site is another alkali metal cation, for example, a salt obtained by substituting the cesium element of the above-described cesium compound with another alkali metal cation element can be used as a raw material.
[0058] When the A site is a nitrogen-containing compound cation such as a methylammonium cation, for example, a neutral compound other than a salt such as methylamine can be used as a raw material. These raw materials can be used in combination of two or more.
[0059] [Perovskite crystal structure B site]
[0060] As the B site of the perovskite crystal structure, a divalent transition metal cation or a divalent cation including a typical divalent metal cation is adopted.
[0061] As the divalent transition metal cation, a scandium cation (Sc 2+ ), a titanium cation (Ti 2+ ), a vanadium cation (V 2+ ), a chromium cation (Cr 2+ ), a manganese cation (Mn 2+ ), an iron cation (Fe 2+ ), a cobalt cation (Co 2+ ), a nickel cation (Ni 2+ ), a copper cation (Cu 2+ ), a palladium cation (Pd 2+ ), an europium cation (Eu 2+ ), or a ytterbium cation (Yb 2+ ) can be adopted.
[0062] As the typical divalent metal cation, a magnesium cation (Mg 2+ ), a calcium cation (Ca 2+ ), a strontium cation (Sr 2+ ), a barium cation (Ba 2+ ), a zinc cation (Zn 2+ ), a cadmium cation (Cd 2+ ), a germanium cation (Ge2+ ), tin cations (Sn 2 + ), or lead cations (Pb 2+ ).
[0063] Among these divalent cations, typical divalent metal cations are preferred in terms of stabilizing the growth of three-dimensional crystals, and tin cations or lead cations are more preferred, and lead cations are particularly preferred from the viewpoint of obtaining high luminous intensity. These divalent cations can be used in combination of two or more, and the perovskite crystal structure can be a so-called double perovskite type.
[0064] When the B site is a lead cation, a lead compound is used as a raw material for synthesizing the nanoparticles, and an appropriate lead compound can be used depending on the synthesis method. As the lead compound, lead chloride, lead bromide, lead iodide, lead oxide, lead hydroxide, lead sulfide, lead carbonate, lead formate, lead acetate, lead 2-ethylhexanoate, lead oleate, lead stearate, lead naphthenate, lead citrate, lead maleate, or lead acetylacetonate is used. When the B site is another divalent metal cation, a salt obtained by substituting the lead element of the above-described lead compound with another divalent metal cation element can be used as a raw material. These raw materials can be used in combination of two or more.
[0065] [X site of perovskite crystal structure]
[0066] As the X of the perovskite crystal structure, monovalent anions including halide anions are used. Examples of the halide anion include fluoride anions (F - ), chloride anions (Cl - ), bromide anions (Br - ), and iodide anions (I - ). In particular, from the viewpoint of forming stable three-dimensional crystals and exhibiting strong luminescence in the visible light region, chloride anions, bromide anions, and iodide anions are preferred. The luminescence color is blue when a chloride anion is used, green when a bromide anion is used, and red when an iodide anion is used.
[0067] Two or more types of halide anions can be used. In particular, when chloride anions, bromide anions, and iodide anions are used in combination, the luminescence wavelength of the nanoparticles can be adjusted to a desired wavelength depending on the content ratio of the anion species. That is, in particular, the combined use of chloride anions, bromide anions, and iodide anions is preferred because a luminescence spectrum covering almost all regions of visible light from blue to red can be obtained while maintaining a narrow half-width, depending on the content ratio of the anion species.
[0068] The X site can contain monovalent anions other than halide anions. Examples of monovalent anions other than halide anions include pseudohalide anions such as cyanide anions (CN - ), thiocyanate anions (SCN - ), and isothiocyanate anions (CNS - ). Depending on the synthesis method, the raw materials for nanoparticle synthesis can be appropriately selected from salts having counter cations at the A site and the B site, such as cesium chloride and lead bromide, and salts having cations other than the above.
[0069] The nanoparticles P in the present embodiment can be manufactured by the following processes. For example, a thermal injection method in which a raw material solution is mixed at a high temperature to produce fine particles, which are then rapidly cooled to obtain a stable product, or a ligand-assisted reprecipitation method in which fine particles are obtained by reprecipitation using the difference in miscibility of the product and the solvent.
[0070] Further, a room temperature synthesis method in which a mixture of non-halide components not containing components for the X site, i.e., a raw material for the A site and a raw material for the B site, and a raw material solution for the X site, which is separately prepared, are mixed to obtain fine particles under mild conditions at around room temperature, is also a manufacturing method to be employed. Further, a mechanochemical method in which product fine particles are obtained by a reaction in which solid raw materials are mechanically mixed by, for example, grinding or ultrasonic treatment, and an in situ synthesis method in which a reaction product is obtained by coating a raw material solution onto a substrate and then performing direct crystal growth, are also manufacturing methods to be employed.
[0071] The ligand described later coordinates to the surface of the nanoparticles P by coexisting during the manufacture of the nanoparticles P, and can stabilize the dispersion.
[0072] (Solvent)
[0073] As the solvent, a low-polarity solvent (low relative dielectric constant solvent) having a relative dielectric constant of a prescribed value or less can be used. The prescribed value is 6.0 or less, and more preferably 4.5 or less.
[0074] Specific examples thereof include aromatic hydrocarbons such as xylene (relative dielectric constant: 2.3) and toluene (relative dielectric constant: 2.4); hydrocarbons such as hexane (relative dielectric constant: 1.9); alicyclic hydrocarbons such as cyclohexane (relative dielectric constant: 2.0); esters such as ethyl acetate (relative dielectric constant: 6.0) and butyl acetate (relative dielectric constant: 5.0); halogenated alkyls such as chloroform (relative dielectric constant: 4.9); and ethers such as diethyl ether (relative dielectric constant: 4.3). These solvents can also be used as a mixture as needed. In such a case, the relative dielectric constant is a weighted average of all the solvents.
[0075] (Ligand)
[0076] In the present embodiment, the ligand 60 is preferably at least one compound or ion selected from the group consisting of a weak acid such as a carboxylic acid, a weak base such as an amine, and salts and ions thereof.
[0077] Examples of the acid include a branched or straight-chain aliphatic acid having 1 to 30 carbon atoms. The alkyl chain can be saturated or unsaturated. In particular, from the viewpoint of solubility and stability to solvents, a straight-chain aliphatic acid is preferred, and oleic acid is further preferred.
[0078] Examples of the base include a branched or straight-chain organic base having 1 to 30 carbon atoms. The alkyl chain can be saturated or unsaturated. In particular, from the viewpoint of solubility and stability to solvents, a straight-chain organic base is preferred, and oleylamine is further preferred.
[0079] The ligand 60 can be composed of a single ligand or a combination of two or more ligands.
[0080] (Amount of ligand with respect to nanoparticle P)
[0081] When the nanoparticle P is 100, the amount of the ligand is preferably 10 or more and 500 or less, more preferably 20 or more and 400 or less, and further preferably 30 or more and 300 or less. When the amount of the ligand is less than 10 or more than 300, the dispersion stability of the nanoparticle P can be insufficient.
[0082] (Associative ligand)
[0083] In the present embodiment, the associating ligand 60 includes a main chain 40 having a plurality of carbon atoms and a polar group 50 having a polarity higher than that of the main chain 40, and includes an associating ligand that self-associates in the solvent 10. The associating ligand 60 can be composed of a low-molecular compound as shown in Fig. 2B , or can be composed of a high-molecular compound as shown in Fig. 2C . Alternatively, both a low-molecular compound and a high-molecular compound can be included (not shown). As shown in Fig. 2C , the self-association can occur intramolecularly, or as shown in Fig. 2D , the self-association can occur intermolecularly. In Fig. 2B , the main chain 40 of the ligand 60 is straight-chain, but the main chain 40 can be a branched skeleton.
[0084] From the viewpoint of more effectively inducing a change to the α phase, the associating ligand 60 is preferably mainly composed of a high-molecular compound.
[0085] The main chain 40 of the low-molecular compound is a straight-chain, branched, or cyclic alkyl group, a straight-chain, branched, or cyclic heteroalkyl group, an aryl group, a heteroaryl group, an aralkyl group, or a heteroaralkyl group. These compounds can be further substituted by a moiety.
[0086] The polar group 50 is constituted by a strong acid such as a sulfonic acid and a phosphonic acid, a strong base such as a quaternary ammonium cation, or a zwitterionic group such as a sulfobetaine, a phosphobetaine, and a carboxybetaine. The polar group 50 can take the form of at least one compound or ion selected from the group consisting of the above-described salts and ions as a component.
[0087] As the high molecular compound, a copolymer (described later) obtained by polymerizing at least two types of monomers can be used.
[0088] (Amount of the associating ligand with respect to the nanoparticles P)
[0089] When the nanoparticles P are 100, the amount of the ligand is preferably 1 or more and 1000 or less, more preferably 10 or more and 800 or less, and further preferably 30 or more and 600 or less. When the amount of the associating ligand is less than 10, the single phase formation effect can not be sufficiently obtained. When the amount of the associating ligand is more than 600, the associating product of the associating ligand can not be well formed in the solvent.
[0090] (Millimoles of the polar group per 1 g of the nanoparticles P)
[0091] The millimoles of the polar group per 1 g of the nanoparticles P are preferably 0.01 to 10, preferably 0.03 to 8, and more preferably 0.1 to 6. When the millimoles of the polar group per 1 g of the nanoparticles P are within the above-described range, the coordination with the nanoparticles P is performed at the same time, and the formation of the single crystal phase is easily performed. When the millimoles are less than 0.01, the formation of the single crystal phase can not be sufficiently performed. When the millimoles are more than 10, the associating product can not be well formed in the low polarity solvent. The millimoles correspond to the content of the polar group contained in 1 g of the nanoparticles P, and is a unit corresponding to x 10 -3 mol.
[0092] <Method for manufacturing a nanoparticle composition>
[0093] The purification method of the nanoparticles of the present application will be described in detail below.
[0094] The purification method of the present application includes the following steps:
[0095] - a step of preparing nanoparticles (A) having a perovskite-type crystal structure as a polymorph and containing a plurality of crystal structures;
[0096] - a step of preparing a ligand solution (B) containing a solvent having a relative dielectric constant of a prescribed value or less and an associating ligand containing a main chain having a plurality of carbon atoms and a polar group having higher polarity than the main chain and self-associating in the solvent; and
[0097] - a step of preparing a nanoparticle dispersion liquid (C) by bringing the nanoparticle P and the ligand solution Q into contact with each other, wherein the step of preparing the nanoparticle dispersion liquid R includes a step of monophasing the crystal structure of the nanoparticle.
[0098] (Step of preparing nanoparticle P)
[0099] The method of preparing the nanoparticle P is as described above. The remaining ligand can be removed as needed by centrifugation or the like.
[0100] (Step of preparing ligand solution Q)
[0101] To prepare the ligand solution Q, the second ligand manufactured by the above method can be dispersed in a second solvent 80. Dispersion can be promoted as needed by ultrasonic treatment or heating or the like.
[0102] (Step of preparing nanoparticle dispersion liquid R)
[0103] To prepare the nanoparticle dispersion liquid R, the nanoparticle P and the ligand solution Q can be mixed. In this case, the ligand solution Q can be mixed with the solid nanoparticle P, or a dispersion liquid in which the nanoparticle P is dispersed in a solvent can be mixed with the ligand solution Q. The dispersion solvent of the nanoparticle P can be the same as or different from the solvent of the ligand solution Q. The dispersion solvent of the nanoparticle P is preferably a solvent having a relative dielectric constant of a prescribed value or less. The prescribed value is preferably 6.0 or less, and more preferably 4.5 or less.
[0104] (Step of selectively increasing the proportion of the content of a prescribed crystal structure among a plurality of crystal structures)
[0105] In the present embodiment, the step of selectively increasing the proportion of the content of a prescribed crystal structure among a plurality of crystal structures preferably includes a step of monophasing the crystal structure of the nanoparticle. The step of selectively increasing the proportion of the content of a prescribed crystal structure among a plurality of crystal structures preferably includes a step of selectively increasing the proportion of the content of a prescribed crystal structure among a plurality of crystal structures. In the method of purifying a nanoparticle 1000, as shown in FIG. 2, a method of verifying a crystal structure 2000 including steps S201 to S209 is performed. The change in the crystal structure of the nanoparticle P by the step of preparing a nanoparticle dispersion liquid R can be verified by performing steps S201 to S209. Fig. 1B
[0106] (First acquisition step S203)
[0107] The first acquisition step S203 includes a step of collecting a first solid component from the nanoparticles P obtained by the step S103, and acquiring information of the crystal structure of the first solid component. The information of the crystal structure of the first solid component is obtained by analysis, for example, by a diffraction angle spectrum of X-ray diffraction or a halo pattern obtained by electron beam diffraction, and the like.
[0108] (Second acquisition step S205)
[0109] The second acquisition step S205 includes a step of collecting a second solid component from the nanoparticle dispersion liquid, and acquiring information of the crystal structure of the second solid component. The method of acquiring the information of the crystal structure of the second solid component is the same as the method of acquiring the information of the crystal structure of the first solid component, but the method is preferably the same as the method of acquiring the information of the crystal structure of the first solid component.
[0110] (Step S207 of verifying the change in the crystal structure)
[0111] The step S207 of verifying the change in the crystal structure verifies the change in the crystal structure of the nanoparticles P due to the step of preparing the nanoparticle dispersion liquid, based on the information of the crystal structure of the first solid component and the information of the crystal structure of the second solid component.
[0112] (Multiple crystal structures)
[0113] Next, the multiple crystal structures of the nanoparticles P prepared in the step S103 are described.
[0114] It is preferable that the multiple crystal structures include the α phase and at least one of the β phase and the γ phase, and the prescribed crystal structure includes the α phase. Here, the α phase is a crystal phase classified in the cubic system. The β phase is a crystal phase classified in the tetragonal system. The γ phase is a crystal phase classified in the orthorhombic (rhombic) system. Among the α phase, the β phase, and the γ phase, the α phase is a high-temperature stable phase.
[0115] The multiple crystal structures include multiple crystal structures having different synthesis temperatures from each other, and the prescribed crystal structure preferably corresponds to a crystal structure having the highest synthesis temperature among the multiple crystal structures.
[0116] The multiple crystal structures can be, for example, crystal structures of AB2X5 and A4BX6, and the like.
[0117] In the step of making the crystal structure of the nanoparticles single-phase, the formation of the single-phase crystal structure of the nanoparticles is preferably verified by performing X-ray diffraction (XRD) measurement on both the first solid component of the nanoparticles P stacked on the substrate and the second solid component of the nanoparticles dispersion liquid R stacked on the substrate. Specifically, the formation of the single-phase crystal structure can be confirmed by a change from two peaks to a single peak of the signals of the β phase and the γ phase or a change from a broad peak to a sharp peak due to peak overlap.
[0118] The effect of the step of selectively increasing the proportion of the content of the prescribed crystal structure among the plurality of crystal structures can be verified by the steps S203 and S205 shown in FIG. 8. Fig. 1B
[0119] The first acquisition step S203 includes collecting the first solid component from a part of the nanoparticles P, and a step of acquiring information of the crystal structure of the first solid component. The second acquisition step S205 includes collecting the second solid component from a part of the nanoparticles dispersion liquid R, and a step of acquiring information of the crystal structure of the second solid component.
[0120] The selective increase in the proportion of the content of the prescribed crystal structure among the plurality of crystal structures due to the step of preparing the mixed liquid R can be verified by the verification step S207 based on the information of the crystal structure of the first solid component and the information of the crystal structure of the second solid component.
[0121] In order to promote the formation of the single-phase crystal structure, it is preferable to perform heating or ultrasonic treatment, or the like. The heating temperature is preferably 30°C to 100°C, and more preferably 40°C to 80°C.
[0122] (Method for manufacturing high molecular compound)
[0123] A method for manufacturing a high molecular compound that can be used as the associating ligand 60 will be described in detail below. The method for manufacturing a high molecular compound is not particularly limited as long as the above structure is obtained, but the high molecular compound can be manufactured by, for example, the following method (i) or (ii).
[0124] That is, examples of the method (i) for manufacturing a high molecular compound include a manufacturing method by manufacturing a monomer having a structural unit including a polar group, and then polymerizing the monomer. Examples of the method (ii) for manufacturing a high molecular compound include a method by synthesizing a polymer main chain, and then binding a polar group to the polymer main chain.
[0125] From the viewpoints of the availability of the monomer and the control of the amount of the functional group, the manufacturing by the method (i) is preferable. Hereinafter, the method for synthesizing a high molecular compound including a zwitterionic group as a polar group will be described in detail using the method (i).
[0126] As a monomer for introducing a polar group to a high molecular compound, a vinyl ether derivative, an acrylic ester derivative, a methacrylic ester derivative, an a-olefin derivative, or an aromatic vinyl derivative, or the like can be used. From the viewpoint of ease of manufacture of the monomer, it is preferable to use an acrylic ester derivative or a methacrylic ester derivative as the monomer.
[0127] The corresponding acrylic ester derivative or methacrylic ester derivative can be manufactured by, for example, the method described in K. Ishihara and others, "Polymer Journal", (Japan), The society of Polymer Science, 1990, Vol. 22, pp. 355-360.
[0128] Examples of the method of polymerizing the above-described monomer include radical polymerization and ionic polymerization, and living polymerization for the purpose of molecular weight distribution control and structure control can also be used. Industrially, it is preferable to use radical polymerization.
[0129] Radical polymerization can be performed by the use of a radical polymerization initiator, light irradiation such as radiation and laser, the combined use of a photopolymerization initiator and light irradiation, or heating, or the like. The radical polymerization initiator can be an initiator that can generate radicals and initiate polymerization, and is selected from compounds that generate radicals by the action of heat, light, radiation, and redox reactions, or the like.
[0130] Examples of the compound include azo compounds, organic peroxides, inorganic peroxides, organometallic compounds, and photopolymerization initiators.
[0131] More specific examples include azo compounds such as 2,2'-azobisisobutyronitrile (AIBN) and 2,2'-azobis(2,4-dimethylvaleronitrile); organic peroxides such as benzoyl peroxide (BPO), t-butyl peroxypivalate, and t-butyl peroxyisopropyl carbonate; inorganic peroxides such as potassium persulfate and ammonium persulfate; and redox initiators such as hydrogen peroxide-iron (II) salt systems, BPO-dimethylphenylamine systems, and cerium (IV) salt-alcohol systems. Examples of photopolymerization initiators include acetophenone systems, benzoin ether systems, and ketal systems. These radical polymerization initiators can be used in combination of two or more.
[0132] The preferable range of the polymerization temperature of the vinyl monomer varies depending on the type of the polymerization initiator used, and polymerization is generally performed at a temperature of -30°C to 150°C, and a more preferable temperature range is 40°C to 120°C.
[0133] The amount of use of the polymerization initiator in this case is 0.1 parts by mass or more and 20 parts by mass or less based on 100 parts by mass of the monomer, and is preferably adjusted to obtain a high molecular compound having a target molecular weight distribution.
[0134] The polymerization method can be any of solution polymerization, suspension polymerization, emulsion polymerization, dispersion polymerization, precipitation polymerization, and bulk polymerization, and is not particularly limited.
[0135] The obtained high molecular compound can be purified as needed. The purification method is not particularly limited, and methods such as reprecipitation, dialysis, column chromatography, and the like can be used.
[0136] Various equipment analysis can be used to identify the structure of the manufactured high molecular compound. As the analysis equipment, a nuclear magnetic resonance device (NMR), a gel permeation chromatograph (GPC), an inductively coupled plasma emission spectrometer (ICP-AES), and the like can be used.
[0137] (Polymerizable Compound)
[0138] The polymerization of the polymerizable compound is promoted by receiving energy such as light and heat, and the compound becomes a component that imparts viscosity to the light-responsive composition and cures it. As the polymerizable compound, a radical polymerizable compound or a cationic polymerizable compound can be used. These compounds can be used alone or in combination of two or more. Alternatively, a photopolymerizable compound or a thermal polymerizable compound can also be used. In the present specification, a form in which the viscosity is increased by the polymerization of the polymerizable compound can be paraphrased as a polymer.
[0139] As the radical polymerizable compound, for example, a monofunctional (meth)acrylate-based compound, a bifunctional (meth)acrylate-based compound, a trifunctional or higher (meth)acrylate-based compound, a hydroxyl group-containing (meth)acrylate-based compound, a carboxyl group-containing (meth)acrylate-based compound, or a vinyl-based compound can be used.
[0140] As monofunctional (meth)acrylate compounds, for example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, benzyl (meth)acrylate, 3,3,5-trimethylcyclohexyl acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, methoxyethyl (meth)acrylate, ethylcarbitol (meth)acrylate, isobornyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (3- ethyloxetanyl-3-yl)methyl (meth)acrylate, or cyclic trimethylolpropane formal (meth)acrylate can be used.
[0141] As difunctional (meth)acrylate compounds, for example, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol 200 di(meth)acrylate, polyethylene glycol 300 di(meth)acrylate, polyethylene glycol 400 di(meth)acrylate, polyethylene glycol 600 di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol 400 di(meth)acrylate, polypropylene glycol 700 di(meth)acrylate, neopentyl glycol di(meth)acrylate, neopentyl glycol PO-modified di(meth)acrylate, EO-modified bisphenol A di(meth)acrylate, PO-modified bisphenol A di(meth)acrylate, or hydroxypivalic acid neopentyl glycol di(meth)acrylate can be used.
[0142] As trifunctional or higher (meth)acrylate compounds, for example, trimethylolpropane tri(meth)acrylate, trimethylolpropane EO-modified tri(meth)acrylate, trimethylolpropane PO-modified tri(meth)acrylate, glycerol propoxy tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tris(acryloyloxyethyl) isocyanurate, or EO-modified pentaerythritol tetraacrylate can be used.
[0143] As vinyl compounds, for example, vinyl acetate, vinyl benzoate, vinyl neopentanoate, vinyl butyrate, vinyl methacrylate, or N-vinylpyrrolidone can be used.
[0144] As the cationic polymerizable compound, a photopolymerization type or a thermal polymerization type can be used. These compounds can be used alone or in combination of two or more. Representative examples of the cationic polymerizable compound include epoxy compounds, oxetane compounds, and vinyl ether compounds.
[0145] The amount of use of the polymerizable compound such as the radical polymerizable compound and the cationic polymerizable compound is preferably 1 to 99 parts by mass, more preferably 3 to 90 parts by mass, and further preferably 5 to 80 parts by mass, based on the total photoreactive composition.
[0146] (Polymerization initiator)
[0147] In the polymerization reaction, a polymerization initiator and a polymerizable compound are generally used together. The polymerization initiator is a compound that generates an active species that initiates the polymerization reaction by active energy ray irradiation or heat, and a known polymerization initiator can be used. Major examples of the active species that initiates the polymerization reaction include a radical polymerization initiator that generates a radical and a cationic polymerization initiator that generates an acid, and they can be used in combination. Examples of the photoradical polymerization initiator that generates a radical by active energy rays include acetophenone-based compounds such as diethoxyacetophenone, 2-hydroxy-2-methyl-l-phenylpropan-l-one, benzyl methyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl) ketone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-l-[4-(methylthio)phenyl]-2-morpholinopropan-l-one, 2-benzyl-2-dimethylamino-l-(4-morpholinophenyl)butane, oligo[2-hydroxy-2-methyl-l-[4-(l-methylethenyl)phenyl]propanone], and 2-hydroxy-l-[4-[4-(2-hydroxy-2-methylpropanoyl)benzyl]phenyl]-2-methylpropan-l-one; benzoin-based compounds such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; phosphine-based compounds such as 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenyl phosphine oxide); and other examples such as phenyl glyoxylic acid methyl ester.
[0148] Among the photoradical polymerization initiators, benzoin-based compounds represented by aminoketones, phosphine-based compounds, and oxime ester compounds are preferred. Depending on the properties required for the cured product, they can be used alone or in combination. The amount of use of the radical polymerization initiator is preferably 0.01 to 100 parts by mass, and more preferably 0.1 to 50 parts by mass, based on 100 parts by mass of the total amount of the solid content in the composition.
[0149] (Other additives)
[0150] In the present embodiment, the photoresponsive composition can be used as needed by mixing with an oxygen scavenger, an antioxidant, a scattering agent such as titanium oxide, a surfactant, an antifungal agent, a light stabilizer, other additives that impart various properties, and a dilution solvent, and the like.
[0151] <Second Embodiment>
[0152] Use Fig. 3A and Fig. 3B A nanoparticle composition 100 according to the second embodiment is described.
[0153] The nanoparticle composition 100 according to the second embodiment includes a nanoparticle 110 having a perovskite-type crystal structure as a polymorph and an associative ligand 140 including a main chain 120 having a plurality of carbon atoms and a polar group 130 having a polarity higher than that of the main chain. At least a portion of the associative ligand 140 is coordinated with the nanoparticle 110 via the polar group 130 to change the crystal structure of the nanoparticle.
[0154] (Nanoparticle)
[0155] The nanoparticle 110 in the present embodiment is a nanoparticle including a nanocrystal having a perovskite-type crystal structure in which A sites (monovalent cations), B sites (divalent cations), and X sites (monovalent anions including halide anions) are structural components as a polymorph. As the structural components, the same components as those of the nanoparticle P described in the first embodiment can be used.
[0156] (Associative Ligand)
[0157] In the present embodiment, the associative ligand 140 includes a main chain 120 having a plurality of carbon atoms and a polar group 130 having a polarity higher than that of the main chain. Further, the associative ligand 140 is coordinated with the nanoparticle 110 via the polar group 130 to change the crystal structure of the nanoparticle 110.
[0158] The associative ligand 140 can be made of a low-molecular compound as shown in Fig. 3A or can be made of a high-molecular compound as shown in Fig. 2B Alternatively, both the low-molecular compound and the high-molecular compound can be included (not shown).
[0159] From the viewpoint of effectively inducing a change to the α phase, it is preferable that the associative ligand 140 be mainly made of a high-molecular compound.
[0160] The main chain 120 of the low-molecular compound is a linear, branched, or cyclic alkyl group, a linear, branched, or cyclic heteroalkyl group, an aryl group, a heteroaryl group, an aralkyl group, or a heteroaralkyl group. These compounds can be further substituted by a moiety.
[0161] The polar group 130 is at least one selected from the group consisting of strong acids such as sulfonic acid and phosphonic acid, strong bases such as quaternary ammonium cation, zwitterionic groups such as sulfobetaine, phosphobetaine, and carboxybetaine, and salts and ions thereof.
[0162] As the high molecular compound, a copolymer obtained by polymerizing at least two types of monomers can be used.
[0163] <Third Embodiment>
[0164] Using Fig. 4A and Fig. 4B A nanoparticle composition according to the second embodiment is described.
[0165] The nanoparticle composition according to the third embodiment includes a solvent 201 having a relative dielectric constant of a prescribed value or less, a nanoparticle 210 having a perovskite crystal structure as a polymorph, and a plurality of ligands 240 each including a main chain 220 having a plurality of carbon atoms and a polar group 230 having higher polarity than the main chain, wherein the plurality of ligands 240 include a first component 250 constituting a reverse micelle-like structure in the solvent 201 and a second component 260 coordinated to a surface of the nanoparticle.
[0166] The plurality of ligands 240 can be made of a low molecular compound as shown in Fig. 4A or can be made of a high molecular compound as shown in Fig. 4B Alternatively, both the low molecular compound and the high molecular compound can be included (not shown).
[0167] From the viewpoint of effectively inducing a change to the α phase, it is preferable that the plurality of ligands 240 be mainly made of a high molecular compound.
[0168] The main chain 210 of the low molecular compound is a linear, branched, or cyclic alkyl group, a linear, branched, or cyclic heteroalkyl group, an aryl group, a heteroaryl group, an aralkyl group, or a heteroaralkyl group. These compounds can be further substituted by a moiety.
[0169] The polar group 230 is at least one selected from the group consisting of strong acids such as sulfonic acid and phosphonic acid, strong bases such as quaternary ammonium cation, zwitterionic groups such as sulfobetaine, phosphobetaine, and carboxybetaine, and salts and ions thereof.
[0170] As the high molecular compound, a copolymer obtained by polymerizing at least two types of monomers can be used.
[0171] (reverse micelle-like structure)
[0172] In the present embodiment, the reverse micelle-like structure is a structure in which the polar groups 230 are at least partially associated with each other by electrostatic interaction in the solvent 201 having a relative dielectric constant of a prescribed value or less. The polar groups 230 do not necessarily have to directly interact with each other, and a trace amount of a polar substance such as water can intervene therebetween. Furthermore, the association can be intermolecular association or intramolecular association. Alternatively, different types of polar groups can be associated with each other by electrostatic interaction.
[0173] <Fourth Embodiment>
[0174] The nanoparticle composition 100, 200 having fluidity effectively expresses the effect of the present application that the α phase is maintained even in the form in which the nanoparticle composition 100, 200 is solidified on a substrate. The nanoparticle composition 200 (100) takes the form of a layer supported by other members, and can thus be paraphrased as a wavelength conversion layer. In the supported form, there are included a laminated form and a dispersed form in which the composition is dispersed in a matrix material. Examples of the wavelength conversion layer include a film, a sheet, or a patterned pixel obtained by coating and solidifying the nanoparticle composition on a supporting member (substrate).
[0175] Fig. 5 A cross-sectional structure of a display device 400 according to the fourth embodiment is shown.
[0176] In the display device 400, the light-emitting layer 410, the dielectric multilayer film 417, and the wavelength conversion layer 420 are laminated in the lamination direction D1. The downstream side in the lamination direction D1 corresponds to the side on which a user is positioned to view an image drawn on the display device. The wavelength conversion layer 420 is distinguished from the wavelength conversion layer corresponding to an adjacent device by a black matrix BM separating the pixels.
[0177] The nanoparticle composition 200 is in a form containing a polymerizable monomer (not shown) as described above. The nanoparticle composition 200 containing the polymerizable monomer is cured together with the polymerizable compound by polymerization such as photopolymerization. The nanoparticle composition 200 is cured and becomes a solid nanoparticle composition 426 supported by the dielectric multilayer film 417. The nanoparticle composition 426 is configured to satisfy a prescribed dimension, thereby constituting the wavelength conversion layer 420 of the display device 400. That is, the wavelength conversion layer 420 is a layer cured by curing the entire nanoparticle composition 200 together with the polymerizable compound 150.
[0178] The light-emitting layer 410 corresponds to a light source that emits light L1 having a first wavelength λ1. The wavelength conversion layer 420 includes an optical coupling surface 422 optically coupled to the light-emitting layer 410 on the side surface of the light-emitting layer 410, and is provided with an extraction surface 424 that extracts secondary light L2 converted by the wavelength conversion layer 420 on the opposite side of the light-emitting layer 410.
[0179] The wavelength conversion layer 420 of the present embodiment receives primary light LI having a wavelength λ1 that has penetrated the dielectric multilayer film 417. The dielectric multilayer film 417 provides the display device 400 with a spectral transmittance characteristic of the primary light from the light-emitting layer 410 and a spectral reflectance characteristic of secondary light L2 having a wavelength λ2 that is emitted at the wavelength conversion layer 420. The wavelength λ2 of the secondary light L2 is longer than the wavelength λ1 of the primary light LI.
[0180] The dielectric multilayer film 417 can be replaced by another optical member that has optical transmittance with respect to light having the first wavelength λ1 emitted by the light-emitting layer 410. The optical member (not shown) can be disposed in front of the extraction surface 424 (on the opposite side of the light-emitting layer 410).
[0181] (Method of forming wavelength conversion layer)
[0182] The method of forming the wavelength conversion layer 420 is not particularly limited, and examples thereof include a method of coating a nanoparticle composition on a substrate, and then curing the film by performing pre-drying as necessary and further performing heating or active energy ray irradiation as necessary. The thickness of the wavelength conversion layer 420 after curing is preferably 0.1 μm to 200 μm, and more preferably 1 μm to 100 μm.
[0183] As the active energy ray in the active energy ray irradiation, an electromagnetic wave that reduces the flowability and accelerates curing by polymerization, crosslinking, or drying, etc. is appropriately selected, such as heat rays, UV rays, visible light rays, near-infrared rays, and electron beams. The light source that applies the active energy ray is preferably a light source having a main wavelength of light in the wavelength region of 100 nm to 450 nm. Examples of such a light source include an ultra-high pressure mercury lamp, a high pressure mercury lamp, a medium pressure mercury lamp, a mercury-xenon lamp, a metal halide lamp, a high-power metal halide lamp, a xenon lamp, a pulsed xenon lamp, a deuterium lamp, a fluorescent lamp, an ND-YAG three-wave laser, an HE-CD laser, a nitrogen laser, an XE-Cl excimer laser, an XE-F excimer laser, a semiconductor-pumped solid-state laser, and an LED light source having an emission wavelength of 365 nm, 375 nm, 385 nm, 395 nm, or 405 nm.
[0184] ((Measurement method))
[0185] Various physical properties can be measured as follows.
[0186] ((Measurement of molecular weight distribution))
[0187] The molecular weight distribution of the high molecular compound can be calculated from monodisperse polymethyl methacrylate by gel permeation chromatography (GPC). The molecular weight can be measured by GPC, for example, as follows.
[0188] The sample was added to an eluent described below so that the sample concentration was 1 mass%, the mixture was left to stand at room temperature for 24 hours to prepare a solution, and the solution was filtered through a solvent-resistant membrane filter having a pore diameter of 0.45 μm to obtain a sample solution, which was measured under the following conditions:
[0189] Apparatus: Agilent 1260 infinity system (manufactured by Agilent Technologies, Inc.);
[0190] Column: PFG analysis linear M column (manufactured by Precision System Science Co., Ltd.);
[0191] Eluent: 2,2,2-trifluoroethanol;
[0192] Flow rate: 0.2 mL / min;
[0193] Oven temperature: 40°C; and
[0194] Sample injection amount: 20 μL.
[0195] In the calculation of the molecular weight distribution of the sample, a molecular weight calibration curve was prepared by using a standard polymethyl methacrylate resin (manufactured by Agilent Technologies, Inc., EasiVial PM Polymer Standard Kit).
[0196] ((Structural analysis of the associative ligand)
[0197] The structural analysis of the associative ligand can be performed using nuclear magnetic resonance (NMR). For example, the spectrum of 1 H-NMR and 13 C-NMR was measured using an ECA-600 (600 MHz) manufactured by JEOL Ltd. In this case, the measurement was performed at 25°C in a deuterated solvent containing tetramethylsilane as an internal standard.
[0198] The ppm shift value (δ value) was read as the chemical shift value in the case where tetramethylsilane serving as an internal standard was set to 0.
[0199] ((Verification method of coordination of the associative ligand with the nanoparticle)
[0200] Whether or not the associative ligand 60 is coordinated with the nanoparticle P can be verified using nuclear magnetic resonance (NMR). For example, the spectrum of 1 H-NMR was measured using an ECA-600 (600 MHz) manufactured by JEOL Ltd. The coordination can be verified by the presence of a signal derived from the betaine structure in the spectrum of 1The δ value of the H signal is confirmed by the offset of the δ value of the associated ligand alone or by the change in the half-value width.
[0201] (Analysis of the association state of associative ligands)
[0202] The association state of associating ligands can be analyzed using NMR or dynamic light scattering (DLS). When using NMR, for example, an ECA-600 (600 MHz) manufactured by JEOL Ltd can be used for measurement. 1 ¹H-NMR. When ligands associate, the chemical shift value of the polar group signal changes from that in the unassociated state. Furthermore, when ligands associate, a broader spectrum is observed overall due to the restriction of molecular motion. If necessary, the association state can also be analyzed in more detail by relaxation time measurements. When using DLS, the association state can be analyzed from the particle size. When associating ligands form larger structures through intermolecular association, particle sizes of approximately several hundred nanometers are observed. In intramolecular association, particle sizes of approximately several nanometers are observed.
[0203] (Analysis of the crystal structure (crystalline phase) of nanoparticles)
[0204] X-ray diffraction (XRD) can be used for crystal structure (crystalline phase) and composition analysis of nanoparticles. For example, the crystal structure and composition can be analyzed by measuring the X-ray diffraction pattern using a RINT 2100 (manufactured by Rigaku Corporation) and comparing it with diffraction patterns in a database. Depending on the shape and size of the sample being analyzed, electron beam diffraction (ED) with a cross-sectional TEM can be used.
[0205] (Verification method for single-phase formation)
[0206] The formation of a single-phase crystal structure (crystalline phase) in nanoparticles can be verified by observing changes in the XRD signal. For example, in nanoparticles with a γ phase, the two signals overlap at a diffraction angle of approximately 30° (2θ), resulting in a large half-width. However, the half-width is reduced by changing the γ phase to an α phase.
[0207] (Compositional analysis of nanoparticles)
[0208] The composition of nanoparticles can also be analyzed using XPS and ICP emission spectroscopy. The molar ratio of A to B can be measured by the signal intensity of XPS, and the concentration of X can be measured by the luminescence intensity in ICP emission spectroscopy (e.g., a CIROS CCD (manufactured by SPECTRO GmbH)).
[0209] ((Amount of ligands and associated ligands relative to nanoparticle P))
[0210] The amount of the ligand with respect to the amount of the nanoparticle P can be determined by TG-DTA measurement and NMR measurement. For example, the amount of the nanoparticle P in the nanoparticle composition is measured by TG-DTA measurement. Subsequently, the amount of the ligand and the amount of the associated ligand in the nanoparticle composition are determined by NMR measurement, respectively, so that the amount of the ligand and the amount of the associated ligand with respect to the amount of the nanoparticle P can be determined.
[0211] ((amount of polar group in associated ligand)
[0212] The amount of the polar group in the associated ligand can be determined by NMR measurement. For example, the amount of the polar group in the associated ligand is measured using ECA-600 (600 MHz) manufactured by JEOL Ltd. 1 H-NMR. The amount of the polar group in the associated ligand is calculated by comparing the signal intensity derived from the polar group and the signal intensity derived from a portion other than the polar group.
[0213] ((millimoles of polar group per 1 g of nanoparticle)
[0214] The millimoles of the polar group per 1 g of the nanoparticle can be calculated from the amount of the nanoparticle P, the amount of the associated ligand, and the amount of the polar group in the associated ligand determined by the above-described methods.
[0215] Examples
[0216] The present disclosure is described in more detail below by way of examples, but the present disclosure is not limited thereto.
[0217] [Manufacture of associated ligand a]
[0218] A reaction vessel equipped with a condenser, a stirrer, a thermometer, and a nitrogen introduction tube was provided. Into the reaction vessel, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonate (0.8 parts), hexyl methacrylate (51.1 parts), azobisisobutyronitrile (3.9 parts), and 2,2,2-trifluoroethanol (900 parts) were charged. Further, the reaction vessel was subjected to nitrogen bubbling for 30 minutes. The resulting reaction mixture was heated at 65°C for 8 hours under a nitrogen atmosphere to complete the polymerization reaction. The reaction liquid was cooled to room temperature, and then water (300 parts) was added thereto to precipitate the product. After centrifugation, the supernatant was removed. The solvent was distilled off under reduced pressure, and then dried under reduced pressure at 50°C under 0.1 kPa or less to obtain the associated ligand a. It was confirmed by NMR measurement that the structural unit including the polar group was included in an amount of 1 mol% of the total monomer units. The weight average molecular weight (Mw) analyzed by GPC was 12500.
[0219] [Manufacture of associative ligand b]
[0220] The associative ligand b was manufactured as in the manufacture of the associative ligand a except that the amounts of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1 -sulfonate and hexyl methacrylate were changed from 0.8 part to 5.9 parts and from 51.1 parts to 48.0 parts, respectively.
[0221] [Manufacture of associative ligand c]
[0222] The associative ligand c was manufactured as in the manufacture of the associative ligand a except that the amounts of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1 -sulfonate and hexyl methacrylate were changed from 0.8 part to 6.8 parts and from 51.1 parts to 47.5 parts, respectively.
[0223] [Manufacture of associative ligand d]
[0224] The associative ligand d was manufactured as in the manufacture of the associative ligand a except that the amounts of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1 -sulfonate and hexyl methacrylate were changed from 0.8 part to 10.2 parts and from 51.1 parts to 45.4 parts, respectively.
[0225] [Manufacture of associative ligand e]
[0226] The associative ligand e was manufactured as in the manufacture of the associative ligand a except that the amounts of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1 -sulfonate and hexyl methacrylate were changed from 0.8 part to 15.2 parts and from 51.1 parts to 42.3 parts, respectively.
[0227] [Manufacture of associative ligand f]
[0228] The associative ligand f was manufactured as in the manufacture of the associative ligand a except that the amounts of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1 -sulfonate and hexyl methacrylate were changed from 0.8 part to 20.3 parts and from 51.1 parts to 39.2 parts, respectively.
[0229] [Manufacture of associative ligand g]
[0230] The associative ligand g was produced as in the production of the associative ligand a except that the amounts of the 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1 -sulfonate and the hexyl methacrylate were changed from 0.8 part to 33.9 parts and from 51.1 parts to 31.0 parts, respectively, in the production of the associative ligand a.
[0231] [Production of associative ligand h]
[0232] The associative ligand h was produced as in the production of the associative ligand a except that the 0.8 part of the 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1 -sulfonate was changed to 10.7 parts of 2-(methacryloyloxy)ethyl-2-(trimethylammonio)ethyl phosphate, and the amount of the hexyl methacrylate was changed from 51.1 parts to 45.4 parts.
[0233] [Production of associative ligand i]
[0234] The associative ligand i was produced as in the production of the associative ligand a except that the 0.8 part of the 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1 -sulfonate was changed to 7.8 parts of 2-[[2-(methacryloyloxy)ethyl]dimethylammonio]acetate, and the amount of the hexyl methacrylate was changed from 51.1 parts to 45.4 parts.
[0235] [Production of associative ligand j]
[0236] To a reaction vessel equipped with a condenser, a stirrer, a thermometer, and a nitrogen introduction tube, [2-(methacryloyloxy)ethyl]trimethylammonium chloride (80% aqueous solution, 7.6 parts), hexyl methacrylate (45.4 parts), azobisisobutyronitrile (3.9 parts), and n-butanol (900 parts) were charged, and then, nitrogen bubbling was performed for 30 minutes. The resulting reaction mixture was heated at 65°C for 8 hours under a nitrogen atmosphere to complete the polymerization reaction. The reaction liquid was cooled to room temperature, and then, water (300 parts) was added thereto to precipitate the product. After centrifugation, the supernatant was removed. The solvent was distilled off under reduced pressure, followed by drying under reduced pressure of 0.1 kPa or less at 50°C. The resulting solid (5 parts) was dissolved in tetrahydrofuran (95 parts), and a solution obtained by dissolving sodium bromide (1.3 parts) in water (2.7 parts) was gradually added thereto, followed by stirring at room temperature for 2 hours. The resulting solution was reprecipitated with water, washed with methanol, and then, vacuum-dried at 50°C for 6 hours to produce the associative ligand j.
[0237] [Production of associative ligand k]
[0238] The associative ligand k was produced in the same manner as in the production of the associative ligand a except that 0.8 parts of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1 -sulfonate was changed to 3.1 parts of methacrylic acid, and the amount of hexyl methacrylate was changed from 51.1 parts to 45.4 parts.
[0239] [Preparation of associative ligand l]
[0240] Octadecyldimethyl(3-sulfopropyl)ammonium hydroxide inner salt (manufactured by Tokyo Chemical Industry Co., Ltd.) was provided as the associative ligand l.
[0241] Table 1 shows the structure, composition, and molecular weight of the produced or provided associative ligands a to k.
[0242] [Table 1]
[0243]
[0244] [Preparation of associative solution]
[0245] (Associative solution of associative ligand a in toluene)
[0246] An associative ligand a (1 part) and toluene (99 parts) were charged into a reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser, and the temperature thereof was raised to 110°C, and the temperature was maintained for 5 minutes. After confirming that the associative ligand a was completely dissolved, the solution was cooled to room temperature to obtain an associative solution a of the associative ligand a in toluene.
[0247] (Associative solutions of associative ligands b to l in toluene)
[0248] The associative solutions b to l of the high-molecular compounds b to l in toluene were produced in the same manner as the associative solution of the associative ligand a in toluene except that the associative ligands b to l were used instead of the associative ligand a.
[0249] (Associative solution of associative ligand d in hexane)
[0250] An associative ligand d (1 part) and hexane (99 parts) were charged into a reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser, and the temperature thereof was raised to 60°C, and the temperature was maintained for 5 minutes. The solution was cooled to room temperature to obtain an associative solution d-2 of the associative ligand d in hexane.
[0251] (Associative solution of associative ligand d in chloroform)
[0252] A reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser was charged with the associated ligand d (1 part) and chloroform (99 parts), and the temperature thereof was raised to 60°C, and the temperature was maintained for 5 minutes. The solution was cooled to room temperature to obtain an associated solution d-3 of the associated ligand d in chloroform.
[0253] (associated solution of associated ligand d in ethyl acetate)
[0254] A reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser was charged with the associated ligand d (1 part) and chloroform (99 parts), and the temperature thereof was raised to 60°C, and the temperature was maintained for 5 minutes. The solution was cooled to room temperature to obtain an associated solution d-3 of the associated ligand d in chloroform.
[0255] [Manufacture of nanoparticle P-1]
[0256] Cesium carbonate (10 parts), oleic acid (27 parts), and 1-octadecene (385 parts) were placed in a flask, and the solution temperature was raised to 120°C, and then degassed for 30 minutes with a vacuum pump. Further, the solution temperature was raised to 150°C under a flow of dry nitrogen, and the temperature was maintained for 30 minutes to obtain a cationic stock solution.
[0257] Separately, lead (II) bromide (10 parts) and 1-octadecene (494 parts) were placed in a flask, and the solution temperature was raised to 120°C, and then degassed for 1 hour with a vacuum pump. Thereto were added oleic acid (89 parts) and oleylamine (31 parts), and then further degassed for 30 minutes with a vacuum pump. Then, instead of a nitrogen flow, the solution temperature was set to 185°C.
[0258] The cationic stock solution (40 parts) was added thereto, and 5 seconds later, the mixture was cooled on ice. Thereto was added ethyl acetate (2000 parts), centrifuged, and the supernatant was removed. The resulting residue was dispersed in toluene, and the solid concentration was adjusted to 1 wt% to obtain a dispersion of nanoparticle P-1 having a perovskite-type crystal structure of CsPbBr3. The proportion of nanoparticle P in the solid component measured by TG-DTA was 53 wt%. When XRD was measured, a signal derived from the γ phase of CsPbBr3and a signal derived from CsPb2Br5were observed.
[0259] [Manufacture of nanoparticle P-2]
[0260] A dispersion of nanoparticles P-2 having a perovskite crystal structure of CsPb(Br / I)3was obtained as in the luminescent nanocrystal dispersion a, except that lead (II) bromide (3.2 parts) and lead (II) iodide (9.3 parts) were used instead of lead (II) bromide (10 parts). The proportion of nanoparticles P in the solid component measured by TG-DTA was 52 wt%. When XRD was measured, a signal derived from the γ phase of CsPbBr3was observed.
[0261] [Manufacture of Nanoparticles P-3]
[0262] Nanoparticles P-3 having a perovskite crystal structure of CsPbBr3were manufactured as in nanoparticles P-1, except that the solution temperature in the manufacture of nanoparticles P-1 was changed to 220°C. The proportion of nanoparticles P in the solid component measured by TG-DTA was 55 wt%. When XRD was measured, signals derived from the α phase and γ phase of CsPbBr3were observed.
[0263] (Example 1)
[0264] Dispersion a (100 parts) of nanoparticles P-1 was placed in a container, and the solvent was distilled off under reduced pressure. Associative liquid a (100 parts) of associative ligand a in toluene was added to the container, and 20 minutes of ultrasonic treatment was performed to promote coordination and a change in the crystal phase, thereby obtaining nanoparticle composition 100-1.
[0265] (Examples 2 to 16 and Comparative Examples 1 to 4)
[0266] Nanoparticle compositions 100-2 to 100-20 were obtained as in Example 1, except that the types of nanoparticles P, associative ligand, and associative liquid were changed to those shown in Table 2.
[0267] [Table 2]
[0268]
[0269] [Assessment]
[0270] [Assessment of Crystal Phase Immediately After Treatment]
[0271] Each solution (50 μL) immediately after treatment was placed in a sample holder, the solvent was removed, and XRD was measured. When nanoparticles P-1 were used, the half-value width of a signal having a maximum value in a diffraction angle (2θ) range of 30° to 31° was measured, and when nanoparticles P-2 were used, the half-value width of a signal having a maximum value in a diffraction angle (2θ) range of 28° to 30° was measured. The assessment criteria are shown below.
[0272] [Assessment Criteria]
[0273] A: half-value width is 0.85° or less;
[0274] B: half-value width is more than 0.85° and 0.9° or less;
[0275] C: half-value width is more than 0.9° and 0.98° or less; and
[0276] D: half-value width is more than 0.98°.
[0277] [Evaluation of crystalline phase after elapse of time]
[0278] The sample on which the evaluation of the crystalline phase immediately after the treatment was performed was left to stand for 1 week at a ventilated place, and then, XRD was measured again. When nanoparticle P-1 was used, the half-value width of the signal having a maximum value in the range of diffraction angle (2θ) of 30° to 31° was measured, and when nanoparticle P-2 was used, the half-value width of the signal having a maximum value in the range of diffraction angle (2θ) of 28° to 30° was measured. The evaluation criteria are shown below.
[0279] [evaluation criteria]
[0280] A: half-value width is 0.85° or less;
[0281] B: half-value width is more than 0.85° and 0.9° or less;
[0282] C: half-value width is more than 0.9° and 0.98° or less; and
[0283] D: half-value width is more than 0.98°.
[0284] Table 3 shows the evaluation results.
[0285] [table 3]
[0286]
[0287] According to Table 3, in the nanoparticle compositions 100-1 to 100-16 according to Examples 1 to 16, the crystalline phase immediately after the treatment was formed as a single phase, as compared with the nanoparticle compositions 100-17 to 100-19 according to Comparative Examples 1 to 3. In addition, even after elapse of time, the obtained single crystalline phase was maintained. These results are considered to be due to the formation of the crystalline phase as a single phase by coordination of the associative ligand 60 with the nanoparticle P having a perovskite structure in the low-polarity solvent 10. In the nanoparticle composition 20 containing the nanoparticle P-3 synthesized at a high temperature, the crystalline phase immediately after the treatment included an α phase, but the α phase could not be maintained over time.
[0288] The present application is not limited to the above-described embodiments, and various modifications and changes can be made without departing from the spirit and scope of the present application. Therefore, in order to inform the disclosed range of the present application, claims are attached.
[0289] This application claims the benefit of Japanese Patent Application No. 2023-083370, filed May 19, 2023, which is hereby incorporated by reference herein in its entirety.
[0290] BRIEF DESCRIPTION OF DRAWINGS
[0291] 1000 Method for producing nanoparticle composition (method for purifying nanoparticles)
[0292] S103 Step of preparing nanoparticles having a plurality of crystal structures
[0293] S105 Step of preparing ligand solution
[0294] S107 Step of preparing nanoparticle dispersion liquid
[0295] S109 Step of selectively increasing the proportion of the content of a prescribed crystal structure among the plurality of crystal structures (step of making the crystal structure of the nanoparticles single phase)
Claims
1. A method for purifying nanoparticles, comprising: The step of preparing nanoparticles, wherein the nanoparticles have a perovskite-type crystal structure as an allotrope and include multiple crystal structures; The step of preparing a ligand solution, wherein the ligand solution comprises a solvent having a relative permittivity below a specified value and an associative ligand, wherein the associative ligand comprises a backbone having a plurality of carbon atoms and a polar group having a polarity higher than that of the backbone and is self-associated in the solvent; and The step of preparing a nanoparticle dispersion by contacting the nanoparticles and the ligand solution with each other, wherein The step of preparing the nanoparticle dispersion includes selectively increasing the proportion of a specified crystal structure among the plurality of crystal structures.
2. The method for purifying nanoparticles according to claim 1, wherein the step of selectively increasing the proportion of a specified crystal structure among the plurality of crystal structures includes the step of making the crystal structure of the nanoparticles monophase.
3. The method for purifying nanoparticles according to claim 1 or 2, wherein the step of selectively increasing the proportion of a specified crystal structure among the plurality of crystal structures includes the step of selectively increasing the proportion of a specified crystal structure among the plurality of crystal structures.
4. The purification method for nanoparticles according to claim 2 or 3, wherein... The plurality of crystal structures include at least any one of α phase, β phase, and γ phase, and The specified crystal structure includes the α phase.
5. The purification method for nanoparticles according to claim 2 or 3, wherein... The plurality of crystal structures includes multiple crystal structures synthesized at different temperatures, and The specified crystal structure corresponds to the crystal structure with the highest synthesis temperature among the plurality of crystal structures.
6. The purification method for nanoparticles according to claim 1 or 2, comprising: The first acquisition step involves collecting a first solid component from the nanoparticles and obtaining information about the crystal structure of the first solid component. and The second acquisition step involves collecting the second solid component from the nanoparticle dispersion and obtaining information about the crystal structure of the second solid component.
7. The method for purifying nanoparticles according to claim 6, comprising the following steps: based on information about the crystal structure of the first solid component and information about the crystal structure of the second solid component, confirming the change in the crystal structure of the nanoparticles caused by the step of preparing the nanoparticle dispersion.
8. The purification method for nanoparticles according to claim 1 or 2, wherein the polar group comprises at least one selected from the group consisting of strong acids, strong bases, zwitterionic groups and their salts and ions.
9. The purification method for nanoparticles according to claim 1 or 2, wherein the polar group comprises at least one selected from the group consisting of sulfonic acid, phosphonic acid, quaternary ammonium cation, sulfobetaine, phosphate betaine, and carboxybetaine.
10. A method for manufacturing a nanoparticle composition, comprising: The step of preparing nanoparticles, wherein the nanoparticles have a perovskite-type crystal structure as an allotrope and include multiple crystal structures; The step of preparing a ligand solution, wherein the ligand solution comprises a solvent having a relative permittivity below a specified value and an associative ligand, wherein the associative ligand comprises a backbone having a plurality of carbon atoms and a polar group having a polarity higher than that of the backbone and is self-associated in the solvent; and The step of preparing a nanoparticle dispersion by contacting the nanoparticles and the ligand solution with each other, wherein The step of preparing the nanoparticle dispersion includes selectively increasing the proportion of a specified crystal structure among the plurality of crystal structures.
11. The method for manufacturing the nanoparticle composition according to claim 10, comprising the step of adding a polymerizable compound to the nanoparticle dispersion.
12. A nanoparticle composition comprising: Nanoparticles with a perovskite-type crystal structure as allotropes; and An associative ligand comprising a backbone having multiple carbon atoms and a polar group having a higher polarity than the backbone, wherein... At least a portion of the associative ligand is coordinated with the nanoparticle via the polar group to alter the crystal structure of the nanoparticle.
13. A nanoparticle composition comprising: Solvents with a relative permittivity below a specified value; Nanoparticles with a perovskite-type crystal structure as an allotrope; Each comprises a main chain having multiple carbon atoms and multiple ligands having a polar group higher than the main chain, wherein the multiple ligands comprise: The first component that forms an antimicelle structure in the solvent; and A second component that is coordinated with the surface of the nanoparticles.
Citation Information
Patent Citations
Medicine delivery assisting system
JP2023083370A